Organophosphate and Pyrethroid Hydrolase Activities of Mutant Esterases from the Cotton Bollworm Helicoverpa armigera - Li, Yongqiang; Farnsworth, Claire A.; Coppin, Chris W.; Teese, Mark G.; Liu, Jian-Wei; Scott, Colin; Zhang, Xing; Russell, Robyn J.; Oakeshott, John G. (PLOS ONE, 2013)
Two mutations have been found in five closely related insect esterases (from four higher Diptera and a hymenopteran) which each confer organophosphate (OP) hydrolase activity on the enzyme and OP resistance on the insect. One mutation converts a Glycine to an Aspartate, and the other converts a Tryptophan to a Leucine in the enzymes’ active site. One of the dipteran enzymes with the Leucine mutation also shows enhanced activity against pyrethroids. Introduction of the two mutations in vitro into eight esterases from six other widely separated insect groups has also been reported to increase substantially the OP hydrolase activity of most of them. These data suggest that the two mutations could contribute to OP, and possibly pyrethroid, resistance in a variety of insects. We therefore introduced them in vitro into eight Helicoverpa armigera esterases from a clade that has already been implicated in OP and pyrethroid resistance. We found that they do not generally enhance either OP or pyrethroid hydrolysis in these esterases but the Aspartate mutation did increase OP hydrolysis in one enzyme by about 14 fold and the Leucine mutation caused a 4–6 fold increase in activity (more in one case) of another three against some of the most insecticidal isomers of fenvalerate and cypermethrin. The Aspartate enzyme and one of the Leucine enzymes occur in regions of the H. armigera esterase isozyme profile that have been previously implicated in OP and pyrethroid resistance, respectively.